Prevalence of self-neglect and related factors among older adults living in Western Turkey: a cross-sectional study - Canan Bulut Ayaz; Melike Yalçin Gürsoy (BMC Geriatrics)
Abstract Background Self-neglect is a serious public health problem affecting older people. This study was conducted to determine the prevalence of self-neglect and related factors in the elderly, which has become more important with the increase in the elderly population. Methods The cross-sectional study included individuals aged 65 years and over. Data were collected via face-to-face interviews using a questionnaire. The questionnaire content included questions related to sociodemographic and health-related characteristics, the Istanbul Medical School Elder Self-Neglect questionnaire, standardized Mini Mental State Examination, Geriatric Depression Scale: Short Form, and Katz Activities of Daily Living Scale. Factors associated with self-neglect were identified using logistic regression analysis. Results In this study, the prevalence of self-neglect in the elderly was 36.6%. In addition, living alone (OR: 2.71), low monthly income perception (OR: 1.86), poor/very poor health perception (OR: 2.30), having mild dementia (OR: 3.00), having severe dementia (OR: 4.54), being severely dependent (OR: 3.39) and lower levels of education (OR: 1.70) were found to be significant factors associated with self–neglect. Conclusion The results of this study showed that approximately one in three elderly people neglected themselves, and that some sociodemographic and health-related characteristics of the elderly were associated with self-neglect.